1986
DOI: 10.1002/polb.1986.090240209
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation temperatures in the ternary system polystyrene/poly(α‐methyl styrene)/cyclopentane

Abstract: Phase separation temperatures of the ternary system polystyrene (PS) (Mw = 1.67 × 104)/poly(α‐methyl styrene) (PαMS) (Mw = 9.0 × 104)/cyclopentane with a blend ratio PS/PαMS = 55/45 have been determined over the polymer concentration range 0.02 ≤ ψPS + PαMS ≤ 0.52, where ψ PS + PαMS is the segment fraction of polymer in ternary system. Phase separation temperatures for the upper critical separation in the ternary system decrease with increasing ψ PS + PαMS over the range 0.1 ≤ ψ PS + PαMS ≤ 0.52. The vapor—liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…However, the Flory-Huggins theory has been shown to be incomplete because the theory introduces as a constant, independent of polymer composition, concentration, or temperature which is contrary to experiment.24•25 The polymer-polymer interaction parameter also depends on the thermodynamic properties of the solution25-indeed, Saeki et al 26 have shown that can assume large positive values for the "compatible" polymers polystyrene and poly-(a-methylstyrene) when in ternary solution with solvents of unequal quality. Extensions to the Flory-Huggins theory have been proposed but these have not been incorporated in the Benmouna theory.…”
Section: Theorymentioning
confidence: 99%
“…However, the Flory-Huggins theory has been shown to be incomplete because the theory introduces as a constant, independent of polymer composition, concentration, or temperature which is contrary to experiment.24•25 The polymer-polymer interaction parameter also depends on the thermodynamic properties of the solution25-indeed, Saeki et al 26 have shown that can assume large positive values for the "compatible" polymers polystyrene and poly-(a-methylstyrene) when in ternary solution with solvents of unequal quality. Extensions to the Flory-Huggins theory have been proposed but these have not been incorporated in the Benmouna theory.…”
Section: Theorymentioning
confidence: 99%
“…T g for pure polystyrene is ∼100 °C, but a 60% mixture of polystyrene in various solvents appears to have a T g below 23 °C . A 60% mixture should remain a one-phase system at 23 °C (estimated from refs and ). A compression of the adsorbed layers to this composition should thus not cause a glass transition or phase separation.…”
Section: Discussionmentioning
confidence: 99%
“…EPLs are thin polymer films (⩽ 5 μ m) deposited onto a surface, intended to extend the qualitative or quantitative limit of detection by attracting organic compounds via chemical and/or physical interactions. The incorporation of such films into chemical sensors has been heavily researched since the late 1980s [68, 69]. EPLs have been demonstrated as efficient and highly sensitive coatings for diverse evanescent waveguide-based optical monitoring systems [7076].…”
Section: Sensor Functionalization For Enhanced Specificitymentioning
confidence: 99%